Sosialisasi Pembuatan Pupuk Kompos Menggunakan Sampah Organik Rumah Tangga - Wahyuni, Fitri; Fitri, Sri; Setiawan, Deri; Acehan, T. Raden (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2025)
As the world's population grows, the enormous amount of waste of all kinds grows beyond human capabilities, thus creating a serious dilemma in managing the enormous amount of waste. One way to overcome this problem is by providing counseling/socialization about making compost from household organic waste in Cot Seunong Village, Montasik District, Aceh Besar Regency. Cot Seunong is a village that has a very potential, strategic, and easily accessible rice fields and plantations, this community service activity is expected to provide further information and motivate housewives to implement organic farming sustainably, with the use of compost fertilizer that is produced by themselves. The Community Service Methods carried out are (1) Counseling about waste management, (2) Practice of making compost fertilizer from household organic waste. After the Community Service is carried out, the community knows and understands the importance of household waste management and the use of compost fertilizer derived from household organic waste and is able to make compost fertilizer from household organic waste independently.